Atenção farmacêutica em idosos com hipertensão participantes da estratégia saúde da família - Flávia Carnavalli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Systemic arterial hypertension in the elderly people is a very common clinical condition, which mainly in recent years has been showing an increase in the number of cases, affecting 55% of Brazilian elderly (≥ 65 years old). It is a disease, which demands high medical and socioeconomic costs arising from its complications, especially when the patient does not adhere to treatment, leading to a critical public health problem. The pharmaceutical care can help in adherence to therapy, as it is a practice with interaction between the pharmacist and patient, which detects problems related to drugs in order to help patients to have a rational pharmacotherapy. In this context, health policies such as the Family Health Strategy in addition to the pharmacotherapeutic follow-up services contribute to the disease prevention and improve the care of elderly people with hypertension. This study was a controlled randomized, prospective clinical trial aimed to evaluate and carry out the pharmacotherapeutic follow-up in elderly patients with hypertension linked to a Family Health Strategy Unit of Araraquara-SP. It had as the primary endpoint: implementing the pharmacotherapeutic follow-up model in elderly patients with systemic arterial hypertension and evaluating its effectiveness in the public health system at the level of Primary Care, specifically in the Family Health Strategy. And as a secondary endpoint: adequating clinical and anthropometric parameters of patients to the ranges using the values described in the Brazilian guidelines as a basis, besides increasing the patients adherence to drug therapy, self-knowledge about the disease and improving the patients quality of life. This study was conducted with 62 registered users in the Family Health Strategy, divided into two groups: control (31) and intervention (31). It was used pharmaceutical care method based on Pharmacist's Workup of Drug Therapy to carry out the pharmacotherapeutic follow-up, ...

A hipertensão arterial sistêmica em idosos é uma condição clínica muito prevalente e que nos últimos anos, principalmente, vem apresentando aumento no número de casos, acometendo 55% dos idosos brasileiros (≥ 65 anos). É uma doença que demanda altos custos médicos e socioeconômicos, decorrentes de suas complicações, principalmente quando o paciente não adere ao tratamento, levando a um problema crítico de saúde pública. A atenção farmacêutica pode ajudar na adesão à terapia, por ser uma prática com interação entre o farmacêutico e paciente, a qual detecta os problemas relacionados aos medicamentos para auxiliar o paciente a ter uma farmacoterapia racional. Neste contexto, políticas de saúde como a Estratégia Saúde da Família com adição dos serviços de seguimento farmacoterapêutico contribuem para a prevenção da doença e melhora os cuidados da população idosa com hipertensão. Este estudo tratou-se de um ensaio clínico controlado, aleatorizado e prospectivo cujo objetivo foi avaliar e realizar o seguimento farmacoterapêutico em pacientes idosos com hipertensão arterial sistêmica vinculados a uma unidade de Estratégia Saúde da Família de Araraquara-SP. Teve como desfecho primário: aplicar o modelo de seguimento farmacoterapêutico em idosos com hipertensão arterial sistêmica e avaliar sua aplicabilidade no sistema público de saúde em nível de Atenção Básica, especificamente na Estratégia Saúde da Família. Como desfecho secundário: adequar os parâmetros clínicos e antropométricos dos pacientes às faixas de normalidade utilizando como base os valores descritos nas diretrizes brasileiras, além de promover nos pacientes aumento da adesão ao tratamento medicamentoso, autoconhecimento sobre a doença e melhorar a qualidade de vida dos pacientes. O presente estudo foi realizado com 62 usuários cadastrados na Estratégia Saúde da Família, divididos em dois grupos: controle (31) e...
Keywords: Hipertensão; Atenção farmacêutica; Medicina social; Medicamentos; Idosos - Assistência farmacêutica; Idosos - Assistência domiciliar; Hypertension